Synopsis: Transforming agriculture for improving food and nutrition security among Nigerian farm households - Ecker, Olivier; Hatzenbuehler, Patrick L.; Mahrt, Kristi (International Food Policy Research Institute, 2018)
The launch of the Agricultural Transformation Agenda (ATA) by the Nigerian Federal Ministry of Agriculture and Rural Development (FMARD) in 2011 represented a shift in strategy toward increasing the agricultural sector share of the Nigerian economy. The successor FMARD strategy document for 2015-2019, the Agriculture Promotion Policy (APP), encompasses many elements of the ATA and is supportive of a continued emphasis on enhancing government’s attention to and support for the agricultural sector. Given the many Nigerians involved in farming, these adjustments in policymaker focus toward boosting general agricultural development, including targeted initiatives for specific crops and industries, could have substantial effects on livelihoods across Nigeria, especially in terms of farm household planting and consumption decisions. Since much smallholder-produced food is consumed at home rather than sold, such changes would influence dietary intakes and nutrition-related health outcomes. Thus, the goals of this study were to: 1) assess current conditions in the country regarding food insecurity and malnutrition; and, 2) determine if the hypothesized linkages between food consumption and various household characteristics (e.g., agricultural production) and market factors (e.g., prices) are observable in household survey data.